2013
DOI: 10.1007/s11557-013-0913-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasmopara invertifolia sp. nov. causing downy mildew on Helichrysum bracteatum (Asteraceae)

Abstract: Plasmopara invertifolia sp. nov. causes severe leaf distortion and necrosis on Helichrysum bracteatum, a beautiful and important ornamental plant for trade in Brazil. This oomycete pathogen is distinguished from other species of Plasmopara on Asteraceae by its smaller sporangia and larger sporangiophores, which justifies the proposition of a new taxon in the genus Plasmopara to accommodate it. The phylogenetic analysis of cox2 gene sequence data supports such placement and also shows that P. invertifolia is cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…Further detailed morphological studies are needed to assess whether the lineages found in this study can be differentiated based on phenotypic characters that characterize cryptic species within the P. halstedii complex. Our molecular data are in line with other molecular studies (see, e.g., Duarte et al, 2014; Rivera, Salgado‐Salazar, Windham, et al, 2016) supporting the suggestion of Novotel'nova (1966) that P. halstedii should be segregated into distinct species. However, without a molecular investigation of the type specimen of P. halstedii it cannot be concluded whether the name P. halstedii needs formal taxonomic action to keep it as a name for the causal agent of SDM.…”
Section: Discussionsupporting
confidence: 92%
“…Further detailed morphological studies are needed to assess whether the lineages found in this study can be differentiated based on phenotypic characters that characterize cryptic species within the P. halstedii complex. Our molecular data are in line with other molecular studies (see, e.g., Duarte et al, 2014; Rivera, Salgado‐Salazar, Windham, et al, 2016) supporting the suggestion of Novotel'nova (1966) that P. halstedii should be segregated into distinct species. However, without a molecular investigation of the type specimen of P. halstedii it cannot be concluded whether the name P. halstedii needs formal taxonomic action to keep it as a name for the causal agent of SDM.…”
Section: Discussionsupporting
confidence: 92%
“…Species of Plasmopara on Asteraceae can be defined by their host range and morphology under a phylogenetic species concept. This study confirms the hypothesis that species of downy mildew on Asteraceae show greater diversity than the broad concept applied to P. halstedii (Choi et al 2009;Constantinescu and Thines 2010;Duarte et al 2014;Spring et al 2003).…”
Section: Plasmopara Halstedii Kf927154supporting
confidence: 86%
“…Systematic studies based on nuclear rDNA and mitochondrial DNA have subsequently begun to delimit taxa in the P. halstedii species complex (Choi et al 2009;Constantinescu and Thines 2010;Duarte et al 2014;Spring et al 2003;Voglmayr and Constantinescu 2008;Voglmayr et al 2004). Species of Plasmopara on Asteraceae can be defined by their host range and morphology under a phylogenetic species concept.…”
Section: Plasmopara Halstedii Kf927154mentioning
confidence: 99%
“…exhibits a high degree of differentiation according to the host species [14]. In addition, it adds evidence to the recently re-appraised view that a narrow species concept reflects the evolutionary history of downy mildews much better than a broad species concept, as exemplified on other species complexes, such as the ones around Bremia lactucae [35][36][37][38][39][40][41], Hyaloperonospora parasitica [42][43][44][45][46][47][48], Peronospora farinosa [7][8][9]49], Peronospora lamii [12,13,50], and Plasmopara halstedii [24,26,[51][52][53]. The downy mildew of I. textori is one of the most common downy mildew diseases throughout South Korea [21] and is common in China [54,55] and Japan [56] where the host plant is also widely distributed.…”
Section: Discussionmentioning
confidence: 99%